Challenges and Opportunities for Maximizing the Utilization of the New Development Bank in Brazil - Bruno De Conti; Cyro Faccin (Vestnik MGIMO-Universiteta)
Initiating its operations in 2016, the New Development Bank (NDB) disbursed close to US$ 14.6 billion by the conclusion of 2021. However, Brazil received only US$ 1.86 billion (12.8%) of this sum, marking it as the recipient of the least funding from the Bank thus far. As the NDB approaches its seventh year of operation, it becomes imperative to assess its lending trajectory to Brazil, scrutinizing both the disincentives and the potential for augmenting loans to the country. With this objective in mind, this article endeavors to delve into the obstacles and opportunities for enhancing the NDB’s utilization in Brazil. Our hypothesis suggests that despite the recent surge in operations, there remains room for advancement, particularly in light of the political developments unfolding in Brazil in 2023.Methodologically, the study hinges on analyzing NDB financial data, conducting interviews with pertinent stakeholders in Brazil, and scrutinizing and contrasting the financing institutional frameworks of the NDB and the Brazilian Development Bank (BNDES). Our findings indicate that: i) access to the BNDES partially offsets the necessity for Brazilian firms to seek loans from the NDB; ii) a rigid institutional framework within the NDB and the Brazilian government impedes project approval and proposition; iii) all loans to Brazil thus far have been denominated in US dollars, diminishing their attractiveness; iv) there has been a lack of encouragement from the Brazilian national government, attributed to the reorientation of Brazilian foreign policy following the 2016 impeachment. Consequently, achieving a more prominent role and usage of the NDB necessitates not only an institutional reassessment of certain approval processes within the Brazilian government but also a more active, assertive, and collaborative stance from the Bank itself.